2017
DOI: 10.1039/c7gc01188a
|View full text |Cite
|
Sign up to set email alerts
|

Selective conversion of bio-derived ethanol to renewable BTX over Ga-ZSM-5

Abstract: The exchanged Ga(iii) sites are the active sites for promoting BTX formation during ethanol conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 33 publications
7
68
0
Order By: Relevance
“…Interestingly, selectivities and yields are almost constant with increasing time on stream, suggesting that a steady state was attained in our timescale (few hours) with the co-presence of zeolite protonic sites and active carbon. The addition of the dehydrogenating activity of Ga 2 O 3 to the protonic Mobil five (H-MFI) zeolite is reported to improve aromatics production from bioethanol [27].…”
Section: Ethanol To Hydrocarbonsmentioning
confidence: 99%
“…Interestingly, selectivities and yields are almost constant with increasing time on stream, suggesting that a steady state was attained in our timescale (few hours) with the co-presence of zeolite protonic sites and active carbon. The addition of the dehydrogenating activity of Ga 2 O 3 to the protonic Mobil five (H-MFI) zeolite is reported to improve aromatics production from bioethanol [27].…”
Section: Ethanol To Hydrocarbonsmentioning
confidence: 99%
“…1. Previously, it was reported that dealkylation of (m)ethylated naphthalenes occurs during thermal degradation, which is supported by model studies on 13 C-labelled methyl arenes. 37 In the presence of a zeolite, the BTX formed by catalytic aromatization of PAH-derived products most likely originates from the alkyl chains of substituted higher aromatics present in the PAH fraction.…”
Section: Resultsmentioning
confidence: 60%
“…7,8 A number of routes have been developed for the catalytic conversion of sugar-derived furanics into aromatics via Diels Alder (DA) addition and subsequent dehydration reactions (i.e., a stoichiometric synthesis approach). [9][10][11][12] Catalytic conversions of bio-based (isobutyl) alcohols, 13,14 ethylene, 15,16 and pinacol-acrolein 17 to aromatics have also been reported. Catalytic pyrolysis, a one-step process with high flexibility in biomass input, offers another promising pathway to aromatics.…”
Section: Introductionmentioning
confidence: 98%
“…Benzene, toluene and xylene (BTX) can be derived from wood and agricultural waste [84]. Anellotech, a US-based company, has scaled up a process that converts biomass, using their Bio-TCat™ technology, into BTX mixtures.…”
Section: Benzene Toluene and Xylenesmentioning
confidence: 99%